Armenia Skills toward Employment and Productivity : Survey Findings (Urban Areas) - Valerio, Alexandria; Herrera-Sosa, Katia; Monroy-Taborda, Sebastian; Chen, Dandan (World Bank, Washington, DC, 2016)
Governments around the world assign top priority to job creation and productivity growth. Developing the right skills among potential and actual workers not only makes capital and labor more productive, it also makes the adoption and invention of new technologies possible. Recent research also indicates that skill acquisition has a long-lasting impact on the trajectory of a person’s life and that inequality in skills is associated with inequality in income. Moreover, the proportion of non-agricultural low-earning jobs is high in Armenia. Low-earning jobs are defined as those that earn less than two-thirds of the median wage. By this criterion, one in four jobs in Armenia falls into this category, which represents a significantly higher share than that in most European countries, where the incidence of low pay is within the 15-20 percent range. The significant presence of informality in non-agricultural sectors is another factor that contributes to the low-productivity and low-earnings employment. To better understand skill shortages in Armenia, this report looks into the current demand for skills from the labor market, together with the landscape of skills formation and utilization in the country, using the newly available data from the World Bank’s Skills Toward Employment and Productivity (STEP) household and employer surveys, which were undertaken in the country between 2012 and 2013. These extensive surveys sampled Armenia’s urban population and firms. Based on these surveys, this report aims to provide a key diagnosis of skills demand and supply issues in Armenia, highlighting a few initial steps that need to be taken to build a highly productive Armenian labor force, one that can contribute to as well as benefit from the accelerated economic growth.